Chronic Cannabis Abuse, Delta-9-tetrahydrocannabinol and Thyroid Function - Bonnet, U. (Pharmacopsychiatry, 2013)
The aim of this study was to obtain rather rare information about the influence of chronic cannabis abuse on thyroid function.Thyroid function tests (TSH, total T3, free T4) of 39 chronic cannabis-dependent subjects (ICD-10) were determined at admission (for in-patient detoxification). In a subgroup, serum levels of thyroid hormones were correlated with the serum levels of delta-9-tetrahydrocannabinol (THC, N=24) and its major metabolites, THC-OH (N=16) and THC-COOH (N=24).All of the tested patients were found to have TSH, total T3 and free T4 levels within the population reference range. The levels of thyroid hormones did not correlate significantly with levels of THC, THC-OH or THC-COOH in serum.These results argue against a relevant influence of chronic cannabis intake on thyroid function in humans.
Keywords: THC; TSH; thyroid hormones; cannabis-dependence